2013
DOI: 10.1155/2013/981984
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Host Biomarkers in Saliva and Serum Samples from Individuals with Suspected Pulmonary Tuberculosis

Abstract: The diagnosis of tuberculosis remains challenging in individuals with difficulty in providing good quality sputum samples such as children. Host biosignatures of inflammatory markers may be valuable in such cases, especially if they are based on more easily obtainable samples such as saliva. To explore the potential of saliva as an alternative sample in tuberculosis diagnostic/biomarker investigations, we evaluated the levels of 33 host markers in saliva samples from individuals presenting with pulmonary tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 39 publications
9
57
3
Order By: Relevance
“…It has been reported that saliva levels of interleukin (IL)-1β, IL-23, ECM-1, HCC1 and fibrinogen are significantly associated with active TB. 53,54 One study 55 showed that some host inflammatory BM were expressed at much higher concentrations in saliva than in the blood.…”
Section: Bm For Diagnosing Active Tb: Immune Protein Host Signatures mentioning
confidence: 99%
“…It has been reported that saliva levels of interleukin (IL)-1β, IL-23, ECM-1, HCC1 and fibrinogen are significantly associated with active TB. 53,54 One study 55 showed that some host inflammatory BM were expressed at much higher concentrations in saliva than in the blood.…”
Section: Bm For Diagnosing Active Tb: Immune Protein Host Signatures mentioning
confidence: 99%
“…Active TB is characterized by inflammation and the upregulation of acute phase proteins, cytokines, chemokines, and matrix metalloproteinases (MMPs) , which in turn can affect T‐cell function and development in the blood, sputum, and at sites of disease. Cavitation, which is a hallmark of adult pulmonary TB disease, is driven by elevated expression of inflammatory matrix metalloproteinase‐1 (MMP‐1) and MMP‐3, which are found at greater levels in sputum and bronchoalveolar lavage fluid from patients with active TB .…”
Section: Inflammation and Tbmentioning
confidence: 99%
“…There is an urgent need for alternative diagnostic tests that are suitable for use in all patient types, especially in resource-poor settings. Tests based on the detection of host inflammatory molecules5 6 may be beneficial, especially when applied to easily available samples such as finger-prick blood or serum.…”
Section: Introductionmentioning
confidence: 99%